Transition from video-assisted thoracoscopic to robotic esophagectomy: a single surgeon's experience. Issue 2 (25th April 2019) - Chao, Yin-Kai; Wen, Yu-Wen; Chuang, Wen-Yu; Cerfolio, Robert J
SUMMARY: Lymph node dissection (LND) along the left recurrent laryngeal nerve (RLN) is a technically challenging part of esophageal cancer surgery, especially after chemoradiotherapy (CRT). Robotic surgery holds promise to increase its safety and feasibility. The aim of this study was to describe a single thoracoscopic surgeon's experience related to the transition from video-assisted esophagectomy (VATE) to robotic esophagectomy (RE)—with a special focus on the safety of left RLN LND. Patients who underwent minimally invasive esophagectomy and RLN dissection following CRT were dichotomized according to the use of robotic surgery (robotic esophagectomy [RE] versus video-assisted thoracoscopic esophagectomy [VATE]). The following parameters were determined: (1) number of dissected nodes, (2) rates of RLN palsy, (3) rates of perioperative complications, and (4) learning curve. Learning curve analysis was performed using the 10-patient moving average (MA) for operation times and with the cumulative sum (CUSUM) method for left RLN LND (target failure rate: 15%). The RE and VATE groups consisted of 39 and 67 patients, respectively. The intraoperative identification of the left RLN was more common in the RE group (97.4%) than in the VATE group (68.7%; P  < 0.001). Postoperative left RLN palsy was significantly more frequent in the VATE group (26.9%) than in the RE group (10.3%; P  = 0.042), with a higher rate of pneumonia in the former (16.4% versus 2.6%; P  = 0.03). The MA chart revealed a downward trend followed by a flattening of the RE operation time at operation number 17 and 29, respectively. CUSUM analysis showed that the left RLN palsy rate decreased to the target rate after 12 operations. We conclude that at least 12 cases are required for a surgeon with prior experience in VATE to safely accomplish left RLN LND through a robotic approach.